2009
DOI: 10.1136/jech.2008.077750
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to interparental violence and psychosocial maladjustment in the adult life course: advocacy for early prevention

Abstract: International audienceEarly family-level and social-level stressors are both assumed to be the components of two main path models explaining the association between exposure to interparental violence in childhood and its long-term consequences on mental health explored through lifecourse epidemiological studies. Aims: To investigate the association between exposure to interparental violence in childhood and mental health outcomes in adulthood when taking into account early family and social stressors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 36 publications
5
54
0
5
Order By: Relevance
“…57 Furthermore, children exposed to interparental violence have a higher risk of mental health disorder in adulthood than those not exposed. 60 In our sample, subjects with CM reported the preference of parents for a daughter. Parental influences, such as mother's preference for a daughter, has been hypothesized to be important in the etiology of GID, 61 through reinforcing cross-gender behavior.…”
Section: Discussionmentioning
confidence: 99%
“…57 Furthermore, children exposed to interparental violence have a higher risk of mental health disorder in adulthood than those not exposed. 60 In our sample, subjects with CM reported the preference of parents for a daughter. Parental influences, such as mother's preference for a daughter, has been hypothesized to be important in the etiology of GID, 61 through reinforcing cross-gender behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic domestic environments such as family conflicts, physical or sexual abuse increase suicide risk increases (99). Some physical or sexual abuse, specifically those produced during childhood, have a strong association with suicidal behavior (71;73).…”
Section: History Of Physical or Sexual Abusementioning
confidence: 99%
“…A fi nal study using data on a probability sample from France found a signifi cant relationship between a retrospective measure of IPV exposure and adult alcohol dependence in a multivariate model controlling for other family processes as well as demographic variables (Roustit et al, 2009). Furthermore, Roustit et al (2009, p. 566) reported the risk of "alcohol dependence was higher in male respondents from high-confl ict families and/or with a parental history of alcoholism" compared with women.…”
Section: Literature Review: Consequences Of Exposure To Intimate Partmentioning
confidence: 99%
“…However, there is equivocal evidence that male and female responses to family-based violence differ (Fergusson and Horwood, 1998;Miller et al, 1993;Widom, 1998). Among the studies reviewed here, those that estimated models separately for males and females found IPV exposure linked to substance use more consistently for males, but only with outcome measures of alcohol use, not illicit drug use (Dube et al, 2002a;Roustit et al, 2009;Trocki and Caetano, 2003). Supporting this pattern of results, a meta-analysis of studies of childhood impact of IPV showed a somewhat larger effect on men, but differences were not clear-cut, owing to variations in sample characteristics (Wolfe et al, 2003).…”
Section: Literature Review: Consequences Of Exposure To Intimate Partmentioning
confidence: 99%
See 1 more Smart Citation